Pengaruh Penerapan Pendekatan Diferensiasi Instruksi terhadap Hasil Belajar Siswa pada Mata Pelajaran IPAS di SD Negeri 17 Palembang - Sulistia, Ayu; Sholeh, Kabib; Syaflin, Sylvia Lara (SENTRI: Jurnal Riset Ilmiah, 2026)
This research is motivated by the problems that occur, namely the learning process does not involve students enough, students' responses are not very focused so that it is difficult to understand the learning. This is due to the use of conventional or uniform learning approaches that do not adapt to students' needs, thus affecting low student learning outcomes, especially in science learning. This study aims to determine the effect of implementing a differentiated instruction approach on student learning outcomes in science subjects at SD Negeri 17 Palembang. The research method used is a ₐ is accepted and H₀ is rejected, which means there is a significant influence of the implementation of the instructional differentiation approach on student learning outcomes. Based on these findings, it can be concluded that the implementation of the instructional differentiation approach has a significant effect on student learning outcomes in the science subject at SD Negeri 17 Palembang.. The research sample consisted of two classes, namely class VA and class VB, which were determined using the type of ) with a ( technique so that all members of the population were used as research samples. The results of the study showed a significant difference between the experimental class and the control class. The experimental class that received learning with a differentiated instruction approach had an average score of 87.44, while the control class that used conventional learning obtained an average score of 61.72. The results of the hypothesis test using the Independent Sample t-Test showed a significance value (2-tailed) of 0.000 < 0.05. Thus, HPretest-Posttest Control Group DesignNonequivalent Control Group DesignQuasi Experimental Designquasi-experimentalTotal Samplingposttestposttest